A positive relationship between harm avoidance and brain nicotinic acetylcholine receptor availability - Storage, Steven (2013)
Prior research indicates that disturbance of cholinergic neurotransmission reduces anxiety, leading to the hypothesis that people with heightened cholinergic function have a greater tendency toward anxiety-like and/or harm-avoidant behavior. We sought to determine if people with elevated levels of harm avoidance (HA), a dimension of temperament from the Temperament and Character Inventory (TCI), have high α4β2* nicotinic acetylcholine receptor (nAChR) availability. Healthy adults (n = 105; 47 non-smokers and 58 smokers) underwent bolus-plus-continuous infusion positron emission tomography (PET) scanning using the radiotracer 2-[18F]fluoro-3-(2(S)azetidinylmethoxy) pyridine (abbreviated as 2-FA). During the uptake period of 2-FA, participants completed the TCI. The central study analysis revealed a significant association between total HA and mean nAChR availability, with higher total HA scores being linked with greater nAChR availability. In examining HA subscales, both ‘Fear of Uncertainty’ and ‘Fatigability’ were significant, based on higher levels of these characteristics being associated with greater nAChR availabilities. This study adds to a growing body of knowledge concerning the biological basis of personality and may prove useful in understanding the pathophysiology of psychiatric disorders (such as anxiety disorders) that have similar characteristics to HA. Study findings may indicate that heightened cholinergic neurotransmission is associated with increased anxiety-like traits.